PENGARUH KOMUNIKASI ORGANISASI DAN KERJASAMA TIM TERHADAP KINERJA KARYAWAN PADA PT NATRINDO SURYA PRIMA - Syinthiani Arifin, Faradhiba; Darmawan, Aulia (Journal of Research and Publication Innovation, 2024)
This research aims to determine the positive and significant influence of organizational communication on employee performance, as well as the positive and significant influence of teamwork on employee performance, and determine the positive and significant influence of dominant variables on the performance of PT Natrindo Surya Prima. The sample used was a saturated sampling technique of 70 employees. Data analysis techniques use descriptive statistics, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t and f hypothesis tests. The results of this research show that: 1) Partially there is a positive and significant influence between organizational communication on the performance of PT Natrindo Surya Prima employees, this can be proven from Y = 15.568 + 0.596X_1 and the value of t_count > t_tabel (6.782 > 1.996) with sig. < 0.05 which is 0.000. 2) Partially there is a positive and significant influence between organizational communication on the performance of PT Natrindo Surya Prima employees, this can be proven from Y = 27.966 + 0.320X_2 and the value of t_count > t_tabel (2.695 > 1.996) with sig. < 0.05, namely 0.009. 3) Simultaneously there is a positive and significant influence between organizational communication and teamwork on the performance of PT Natrindo Surya Prima employees, this can be proven from Y = 10.825 + 0.539X_1 + 0.192X_2, a correlation value of 0.709, a coefficient of determination value of 50.2 %, as well as the value of f_count > f_table (33.768 > 3.130) and significance < 0.05 (0.000 < 0.05).